Methodological contributions for the fightind fraud: A multidisciplinary challenge - Ferrer-Sapena, Antonia; Sánchez-Pérez, Enrique A. (Anuario ThinkEPI, 2018)
State of the art scientific methods can be used against financial fraud, mainly of a technical nature (computer, economic, mathematical). Although some of the scientific areas involved are not related to technology, such as sociology, it is important that all disciplines provide useful tools to detect fraud. The detection and prevention of financial fraud is a multidisciplinary task, so the solution to this urgent problem needs to be provided by multidisciplinary teams.